Emergence of firms: A sociogeographic demand side perspective - Karl Wennberg; Karin Hellerstedt (European Regional Science Association (ERSA), 2010)
This paper investigates the contextual conditions affecting the entry, growth and exit of knowledge intensive firms. On the aggregate or regional level, entry and exit are often intimately related. We suggests that the entrepreneurial process by which individuals engage in the start, the growth, and the exit of a firm is strongly path-dependent. Second, based on the importance of initial conditions at the regional level, we present empirical analysis on how characteristics of the economic milieu of regions influence firm births. The data material provides information on all knowledge intensive start-ups across the 286 Swedish municipalities between 1994 and 2002. We present an empirical model that captures both supply- and demand-side factors, with a specific emphasis on the demand side. We address the imperative role of initial conditions during firm founding, as these are strongly emphasized by I/O economics, organizational ecology, and entrepreneurship research alike. We describe and explain the substantial variation in start-up rates across municipalities and over time. The paper advanced econometric analysis where we use a number of variables derived from our theoretical framework to formulate and test a model of regional start-up rates. The model is tested on separate samples of services firms and manufacturing firms, yielding interesting results that are in line with the theories of organizational ecology and economic geography, but with somewhat stronger results for start-ups in services. Analyses of firm growth an survival further shows that the factors present during founding are strongly path-dependent, but differ for medium-growth and high-growth firms, and for firms exiting by closure and firms exiting by merger.
Keywords: 330